2008
DOI: 10.1002/dvg.20402
|View full text |Cite
|
Sign up to set email alerts
|

Real time monitoring of BMP Smads transcriptional activity during mouse development

Abstract: Bone morphogenetic protein (BMP) signaling is a key pathway in the patterning and development of organisms as diverse as fruit fly and humans. However, the determination of net BMP signaling, paramount to understanding organogenesis, is limited to the analysis of fixed material. We generated a transgenic mouse that reports the transcriptional response of BMP Smad activation by coupling a well established BMP response element (BRE), isolated from the Id1 promoter, to green fluorescent protein (BRE:gfp). We moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 57 publications
4
76
0
Order By: Relevance
“…3e). Consistently, although Smad4 is ubiquitously expressed at E10.5, its localization is predominantly nuclear in the AV canal3233. Taken together, the data indicate that AV canal-specific regulatory regions that harbour the GATA elements direct complex formation of Gata4, Smad4 and Hat, implicating these factors in AV canal-specific gene activity in vivo .…”
Section: Resultssupporting
confidence: 58%
“…3e). Consistently, although Smad4 is ubiquitously expressed at E10.5, its localization is predominantly nuclear in the AV canal3233. Taken together, the data indicate that AV canal-specific regulatory regions that harbour the GATA elements direct complex formation of Gata4, Smad4 and Hat, implicating these factors in AV canal-specific gene activity in vivo .…”
Section: Resultssupporting
confidence: 58%
“…In contrast, in nearby LECs, pSMAD1/5/8 staining was largely absent, supporting our idea that BMP2 signaling activity is attenuated in LECs during development (Figure 4D). Similarly, in Tg(BRE:EGFP ) 36 transgenic mouse embryos, where BMP signaling activity can be measured by the expression level of EGFP, we found that EGFP expression was similarly reduced in LECs compared with BECs within CVs (Figure 4E and 4F). Taken together, our data allude to an intriguing possibility that BMP2 signaling may need to be suppressed to allow the emergence of LECs.…”
Section: Resultssupporting
confidence: 57%
“…On ligand binding, activated type I BMP receptors phosphorylate Smad transcription factors SMAD1, SMAD5, and SMAD8, which along with the receptor-independent SMAD protein, SMAD4, translocate to the nucleus and regulate the expression of the target genes, such as the inhibitor of DNA-binding (Id) gene family. 36 In addition to the SMAD-dependent pathway, BMP ligands can transduce signaling via MAP kinase pathways. 37 During vascular development, BMP signaling seems to possess a context-dependent function to regulate diverse aspects of EC behaviors.…”
mentioning
confidence: 99%
“…85,86 The epicardium has been shown to serve as an important reservoir of cardiac fibroblasts and vascular smooth muscle progenitors in the developing heart, and plays an important role in cardiac repair after injury 87 . BMP signal transduction has been demonstrated in the atrioventricular canal, 88,89 and to a lesser extent in the cardiac crescent 8890 using BMP reporter mice, which harbour a BMP responsive element that regulates the reporter genes lacZ or GFP . BMP2 and BMPR-1A are both expressed in the cardiac crescent; deletion of BMPR-1A in the cardiac mesoderm results in embryos that lack the cardiac crescent and cardiomyocytes, suggesting a role for BMP in early cardiomyocyte formation.…”
Section: H1 Bmps and The Cardiovascular Systemmentioning
confidence: 99%